Polyhydroxyalkanoates: biodegradable polymers and plastics from renewable resources - Koller, Martin (Materiali in tehnologije, 2013)
Polyhydroxyalkanoates (PHAs) attract considerable attention as sustainable "green plastics" with a real potential to replace their petrol-based competitors in some applications in the not-too-distant future. To reach this goal PHAs must be able to compete with the established petrol-based plastics in both technical and economic terms. The current PHA production is based on prized substrates of high nutritional value such as sucrose, starch or vegetable oils. An alternative, carbon-rich industrial waste can be used as a suitable feedstock. This would contribute to making PHAs economically competitive and would avoid the conflict with human nutrition or animal feeding. Consequently, the decision about the location of the PHA-production facilities depends on the preferable in-house availability of such waste streams. The issue of competitive, large-scale PHA production in Europe was the topic of the ANIMPOL and the WHEYPOL projects. Both intended to develop novel processes for the transformation of abundant, locally available, renewable wastes. In the ANIMPOL case, waste lipids from slaughterhouses are converted to glycerol and a mixture of saturated and unsaturated fatty acid esters (FAEs), better known as biodiesel. The production of saturated FAEs is 50 000 t per year in Europe, decreasing the biodiesel performance as an engine fuel. However, within the project it was demonstrated that they can be efficiently metabolized to PHAs. In the WHEYPOL project attention was focused on 1.4 x 10sup8 t per year of whey from dairies. This waste is of limited use and causes environmental concern. However, lactose, the main carbohydrate found in whey, can be used as a substrate in the WHEYPOL bioprocesses. These strategies demonstrate the feasibility of making "green plastics" competitive by integrating their manufacturing directly into the existing production lines, where the convertible waste streams accrue.
Keywords: polihidroksialkanoati; biodizel; biopolimeri; lipidi; sirotka